Application of electromagnetic fields for intensification of heat and mass exchange in combined gas-liquid processes - Nikolsky, Valeriy; Oliynyk, Olga; Yaris, Vadim; Reshetnyak, Irina (Eastern-European Journal of Enterprise Technologies, 2017)
To date, thermal rectors with submersible combustion devices with efficiency of more than 100 % relative to the lowest heat of combustion are known. This method of heating is more universal and energy efficient due to the absence of heat losses in transportation and maximum utilization of the carrier heat. This opens up broad prospects for the use of these energotechnological facilities in residential gas heating systems. This work has studied the effect of electromagnetic fields having intensity gradient in the direction of motion of the contacting phases on the process of mass transfer between counter-current-moving gas and liquid phases. It was shown that the optimal method of intensification of heat and mass transfer in the submerged combustion devices is oscillation of the contacting phases under action of an electric spark discharge. Design solutions were proposed for intensifying the heat and mass transfer process and increasing the energy efficiency of operation of thermal reactors with the submersible combustion devices. To evaluate the effect of magnetic and electric fields upon their application, it was proposed to use the developed vibrofrequency measuring transducer with a cylindrical-type resonator. Application of such control method makes it possible to measure total frequency-modular oscillations of the contacting phases. In this case, there is no need to control characteristics of magnetic and electric fields and assess their individual effects on the intensity of oscillations in the contacting gas-liquid phases.